2012
DOI: 10.1007/s10584-012-0405-9
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating snow cover in an alpine bog: effects on ecosystem respiration and nutrient content in soil and microbes

Abstract: Snow amount is expected to decline in the Northern hemisphere as an effect of climate warming. However, snow amount in alpine regions will probably undergo stronger interannual fluctuations than elsewhere. We set up a short-term (1 year) experiment in which we manipulated snow cover in an alpine bog, with the following protocol: snow removal at the end of winter; snow removal in spring; snow addition in spring; removal of all aboveground plant tissues with no snow manipulation; no manipulation at all. We measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Snowmelt promotes soil moisture which is in favor of plant growth [ 26 ] but melting of snow can also take more nutrients away stored in the snowpack before plants need them [ 27 , 28 ]. Supplement snowfall stimulates NEP and GEP simultaneously in the mixed prairie [ 29 , 30 ], but has no effect on ecosystem respiration in an alpine bog [ 31 ]. However, few studies have focused on the effect of snowfall on WUE in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Snowmelt promotes soil moisture which is in favor of plant growth [ 26 ] but melting of snow can also take more nutrients away stored in the snowpack before plants need them [ 27 , 28 ]. Supplement snowfall stimulates NEP and GEP simultaneously in the mixed prairie [ 29 , 30 ], but has no effect on ecosystem respiration in an alpine bog [ 31 ]. However, few studies have focused on the effect of snowfall on WUE in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies in both a boreal peatland and a boreal forest found that winter soil frost could influence the soil dissolved organic carbon concentration during the subsequent growing season (Haei et al, 2010(Haei et al, , 2013Agren et al, 2012), which may affect the amount of C substrates available for heterotrophic respiration. In addition, C decomposer communities are sensitive to soil frost (Sulkava & Huhta, 2003;Haei et al, 2011;Bombonato & Gerdol, 2012;Aanderud et al, 2013) and any change in such communities may substantially influence CO 2 production and, thus, emissions during the growing season.…”
Section: Introductionmentioning
confidence: 99%
“…Because methane released from these wetland areas is of microbial origin [9][10][11][12][13], it is important to increase our understanding of the associated microbial communities. The southern region of the United States is of special interest as mid-latitude wetlands are predicted to dramatically increase methane gas release as climate warming occurs [14][15][16].…”
Section: Introductionmentioning
confidence: 99%